Comparative Analysis of Short- and Long-Read Sequencing of Vancomycin-Resistant Enterococci for Application to Molecular Epidemiology - Oh, Sujin; Nam, Soo Kyung; Chang, Ho Eun; Park, Kyoung Un (Frontiers in Cellular and Infection Microbiology, 2022)
Vancomycin-resistant enterococci (VRE) are nosocomial pathogens with genetic plasticity and widespread antimicrobial resistance (AMR). To prevent the spread of VRE in the hospital setting, molecular epidemiological approaches such as pulsed-field gel electrophoresis and multilocus sequence typing have been implemented for pathogen outbreak surveillance. However, due to the insufficient discriminatory power of these methods, whole-genome sequencing (WGS), which enables high-resolution analysis of entire genomic sequences, is being used increasingly. Herein, we performed WGS of VRE using both short-read next-generation sequencing (SR-NGS) and long-read next-generation sequencing (LR-NGS). Since standardized workflows and pipelines for WGS-based bacterial epidemiology are lacking, we established three-step pipelines for SR- and LR-NGS, as a standardized WGS-based approach for strain typing and AMR profiling. For strain typing, we analyzed single-nucleotide polymorphisms (SNPs) of VRE isolates and constructed SNP-based maximum-likelihood phylogenies. The phylogenetic trees constructed using short and long reads showed good correspondence. Still, SR-NGS exhibited higher sensitivity for detecting nucleotide substitutions of bacterial sequences. During AMR profiling, we examined AMR genes and resistance-conferring mutations. We also assessed the concordance between genotypic and phenotypic resistance, which was generally better for LR-NGS than SR-NGS. Further validation of our pipelines based on outbreak cases is necessary to ensure the overall performance of pipelines.